Manufacturing 2002
DOI: 10.1115/imece2002-32872
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Management in Reconfigurable Manufacturing Systems With Stochastic Market Demand

Abstract: An optimal solution, based on Markov Decision Theory, is presented for the capacity management problem in Reconfigurable Manufacturing Systems with stochastic market demand with a time delay between the time capacity change is ordered and the time it is delivered. The optimal policy in this paper is presented as optimal boundaries representing the optimal capacity expansion and reduction levels. The effects of change in the cost function parameters and the delay time on the optimal boundaries are presented for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…This represents the unit cost to maintain the current level of system functionality available in period k. (3) represents the management cost for expanding or reducing the system functionality. A similar function has been proposed by Asl and Ulsoy (2002a) in their capacity expansion and reduction problem. The following equation provides a formal definition.…”
Section: F O R P E E R R E V I E W O N L Ymentioning
confidence: 91%
“…This represents the unit cost to maintain the current level of system functionality available in period k. (3) represents the management cost for expanding or reducing the system functionality. A similar function has been proposed by Asl and Ulsoy (2002a) in their capacity expansion and reduction problem. The following equation provides a formal definition.…”
Section: F O R P E E R R E V I E W O N L Ymentioning
confidence: 91%
“…Ref. [9] presents an optimal solution to the capacity management problem in Reconfigurable Machining Systems [10] using stochastic market demand with time delay between the time capacity change is ordered and the time it is delivered, based on the Markov Decision Theory. Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Some researchers are of the opinion that it is much more important to decide a suitable policy of when, how, and how much to reconfigure the production system, under unreliable market demand. Further, they argued that it is not always beneficial to opt for high degree of reconfiguration very often as it would not always have economic benefits on ramp up time and associated costs (Asl & Ulsoy, 2002a, 2002b. It can be concluded that to have successful application of RMS, work must be done to develop strategies and techniques which would decrease this delay and improve the ramp up time of new configurations to improve system's performance (Dief & ElMaraghy, 2006b).…”
Section: Ramp-upmentioning
confidence: 99%
“…Dynamic approach towards capacity scalability modelling based on feedback control for RMS was proposed by Asl and Ulsoy (2002a). ElMaraghy (2006b, 2007b) also developed a dynamic model for capacity scalability for RMS.…”
Section: Scalabilitymentioning
confidence: 99%
See 1 more Smart Citation